Technology-Driven Approaches to Tackle the Antimicrobial Resistance: A Scoping review - Jasani, Krishna; Joshi, Krupal; Karthikeyan, Venkatesh; Aggarwal, Pradeep; Saini, Narendra (Indian Journal of Community Health, 2025)
Antimicrobial Resistance (AMR) is an escalating global health threat that demands novel and strategic interventions to curb its progression. This review examines how technology-based interventions can help tackle antimicrobial resistance (AMR) within community settings Focused interventions include mobile apps for antibiotic education, telemedicine platforms for monitoring antibiotic use, artificial intelligence (AI) applications for AMR awareness, and the development of low-cost diagnostic kits to ensure rational drug use. These technologies promise to empower communities, improve healthcare delivery, and mitigate the misuse of antibiotics.